Prediksi Tingkat Kepuasan Pasien Terhadap Pelayanan Fisioterapi Menggunakan Metode Algoritma C4.5 - Eugene Florencia; Anta Noviandri; Satrio N. P; Zidni Ilman Khatami; Cut Aida Rahmania (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
In this journal, the level of patient satisfaction with physiotherapy services is predicted using the C4.5 algorithm. The aim of this research is to create a predictive model based on patient feedback to help hospitals or healthcare facilities enhance the quality of physiotherapy services. Data collected from this study includes various variables such as age, patient name or gender, duration of physiotherapy services, health status, and patient name. This data is processed and constructed using the C4.5 algorithm. The research results indicate that the C4.5 algorithm can accurately predict the level of patient satisfaction with physiotherapy services. This model can assist healthcare providers in improving efficiency and patient satisfaction. Furthermore, the model can aid in making better decisions on how to enhance physiotherapy services and ensure patient satisfaction. The conclusions of this research can help healthcare facilities improve physiotherapy services and ensure patient satisfaction